دراسة مقارنة لنماذج الجدارة الائتمانية - العمار, رضوان; قصيري, حسين (Latakia University Journal - Economic and Legal Sciences Series, 2016)
إن استخدام نماذج الجدارة الائتمانية هو من الأساليب المستخدمة في تقييم عملاء القروض والتسهيلات المصرفية في البنوك التجارية, ويتمثل الهدف الرئيس لدراسة الجدارة الائتمانية في التعرف على إمكانية العميل المستقبلية في سداد الائتمان الممنوح وفوائده, وقدمت العديد من نماذج الجدارة الائتمانية, وكانت هذه النماذج في حالة تطور مستمر من حيث المتغيرات التي تضمنتها, لذلك فقد سعى الباحث إلى دراسة أهم هذه النماذج والمقارنة بينها للوصول إلى النموذج الأكثر شمولاً, والذي يمكن استخدامه في دراسة جدارة العملاء الائتمانية كأداة لتجنب المخاطر الائتمانية المستقبلية في البنوك العامة والخاصة العاملة في سورية.تنبع مشكلة البحث من كون منح الائتمان دون دراسة جدارة العملاء هو أمر يترتب عليه مواجهة مخاطر تتمثل في التعثر المستقبلي في سداد الائتمان، وهو ما يتطلب الإلمام بكافة عوامل الجدارة الائتمانية للحد من المخاطر الناجمة عن منح الائتمان سواءً منها التي تتعلق بالمصرف أو العميل أو المتغيرات الأخرى الخارجة عن سيطرة الطرفين.ويهدف البحث إلى التعرف على مفهوم الجدارة الائتمانية ومبررات دراستها, وعرض أهم نماذجها, وإجراء مقارنة بين النماذج وتحديد أوجه التشابه والاختلاف بينها, وقد تم الاعتماد على المنهجين التاريخي والوصفي التحليلي في عرض نماذج الجدارة الائتمانية, إضافةً إلى المنهج الإستقرائي بغية الوصول إلى النموذج الأكثر شمولاً لمتغيرات الجدارة الائتمانية الذي سيوصى باتباعه في معرض اتخاذ القرارات الائتمانية.وقد توصل الباحث إلى مجموعة من النتائج أهمها أن يتلائم نموذج الجدارة الائتمانية مع بيئة التطبيق, وأن يكون النموذج محيطاً بالعوامل المالية والشخصية للعميل المقترض, وأن أكثر نماذج الجدارة الائتمانية إحاطةً بهذه العوامل هو نموذج 18C's , وبناءً عليه ذلك فقد اوصى الباحث باعتماد هذا النموذج لدراسة الجدارة الائتمانية لعملاء القروض في المصارف العامة والخاصة العاملة في سورية.The use of the creditworthiness models is one of the used methods in the evaluation of bank loans and facilities clients in commercial banks,The main objective of creditworthiness study is to identify the future potential of the customer to repay the Granted credit and interest, many creditworthiness models had been provided, These models have been in a constant development of the variables included, And it has sought a researcher to study the most important of these models and compare them to gain access to the most comprehensive model, which can be used in the study of the customer's creditworthiness as a tool to avoid future risks at public and private banks in syria.Research problem stems from the fact that the granting of credit without study the creditworthiness of clients leads to face risks of future defaults in credit repayment, This requires knowledge of all factors of the creditworthiness to reduce the risks resulting from the granting of credit, both of which related to the bank or the client or other variables beyond the control of the parties.The research aims to identify the concept of creditworthiness and its Justification, and display the most important models, and a comparison between models and identify similarities and differences among them, it has been relying on the historical and descriptive and analytical approaches in the presentation of the creditworthiness of models, in addition to the inductive approach in order to access to the most comprehensive variables creditworthiness to be recommended to follow it during the credit decision making model.The researcher reached a set of results most important is the need to provide a model creditworthiness fits with the application environment, and that the form is familiar with financial and personal factors for the client borrower, and the more creditworthy models briefing these factors is the 18C's model, Accordingly, the researcher recommended the adoption of this model to study the creditworthiness of loan clients in the public and private banks operating in Syria.